FAKTOR YANG MEMPENGARUHI KEPUASAN COMPLAINT HANDLING TERHADAP DAN LOYALITAS KONSUMEN - Jatmiko, M. Roby (STIE Totalwin Semarang, 2014)
Academics as well as managers have long been interested in the role of satisfaction with complaint handling (SATCOM) in shaping customersâ attitudes and repurchasing decisions. This interest has generated a widespread belief that SATCOM is driven by the perception that the complaint handling process is just. To test how SATCOM is modulated by distributive, interactional, or procedural justice, we performed a meta-analysis of 60 independent studies of the antecedents and consequences of SATCOM. Results indicate that SATCOM is affected most by distributive justice, then by interactional justice, and only weakly by procedural justice. We also find that SATCOM mediates the effects of justice dimensions on word-of-mouth. However, contrary to com-mon belief, SATCOM does not mediate the effects of justice dimensions on overall satisfaction and return intent. We draw on our results to suggest several avenues for further research.